Understanding the mechanism of acupuncture in acute cerebral infraction through a proteomic analysis: protocol for a prospective randomized controlled trial - Cao, Jiangpeng; Du, Yuanhao; Yin, Xiumei; Zheng, Na; Han, Jiawei; Chen, Linling; Jia, Lanyu (Frontiers in Neuroscience, 2024)
Background: Acute cerebral infarction (ACI), being the predominant form of ischemia, presents challenges in terms of limited effectiveness of various treatments in improving neurological function.Although acupuncture shows promise in addressing ACI, the availability of high-quality evidence regarding its efficacy, safety, and underlying mechanism remains insufficient. In this study, we design a multicenter, prospective, single-blind, randomized controlled trial, with the aim of evaluating the efficacy and safety of acupuncture for ACI and making attempt to unveil the molecular mechanisms by proteomic.Methods: A total of 132 patients involving in four hospitals will be randomized in a 1:1 :1 ratio into acupuncture group, control group and sham acupuncture group. All the patients will receive basic treatment, and the patients in acupuncture group and sham acupuncture group will also receive either acupuncture treatment or sham acupuncture treatment at six sessions weekly, for a 2-week period, and followed by 3 months of follow-up. The primary outcome will be the change in the National Institute of Health stroke scale (NIHSS) scores after treatment. Secondary outcomes will include the Fugl-Meyer Assessment (FMA) scale scores and Barthel Index (BI). Adverse events that occur during the trial will be documented. To discover differentially expressed proteins (DEPs) and their roles between the ACI subjects and healthy controls, we will also perform 4D-DIA quantitative proteomics analysis, and the DEPs will be confirmed by Enzyme-linked immunosorbent assay (ELISA). This study was approved by the Institutional Review Board of the First Teaching Hospital of Tianjin University of Traditional Chinese Medicine (TYLL2023043). Written informed consent from patients is required. This trial is registered in the Chinese Clinical Trial Registry (ChiCTR2300079204). Trial results will be published in a peer-reviewed academic journal.The results of this study will determine the preliminary efficacy and safety of acupuncture in ACI patients, and whether the mechanism of this form of non-pharmacologic stimulation is mediated by a novel therapeutic target for neurorehabilitation through our proteomic analysis.